2019
DOI: 10.2174/1874944501912010387
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Media Lifestyle Interventions on Health Behaviour: A Study on Patients with Major Depressive Disorders and Family Caregivers

Abstract: Background: The World Health Organisation (WHO) predicts that depression will be the second leading cause of diseases by 2020. If depression is not properly treated, it can develop into a depressive disorder and increase the risk of suicide.Besides biopsychosocial factors, lifestyle is said to be a major cause of this disease and has led to an increase in its prevalence. Objective: The objective of this study was to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 90 publications
1
15
0
1
Order By: Relevance
“…On a comparative note, recall predicted health behaviour more than exposure. Our results extend those of Uittenhout (2012) and Jattamart and Leelasantitham (2019), who examined the impact of social media on health behaviour without looking at the role of exposure and recall together. Therefore, in the current study, we have shown that exposure and recall are essential predictors of the effectiveness of YouTube animated cartoons on COVID-19 and on health behaviour.…”
Section: Discussion Of Findingssupporting
confidence: 84%
See 1 more Smart Citation
“…On a comparative note, recall predicted health behaviour more than exposure. Our results extend those of Uittenhout (2012) and Jattamart and Leelasantitham (2019), who examined the impact of social media on health behaviour without looking at the role of exposure and recall together. Therefore, in the current study, we have shown that exposure and recall are essential predictors of the effectiveness of YouTube animated cartoons on COVID-19 and on health behaviour.…”
Section: Discussion Of Findingssupporting
confidence: 84%
“…Fletcher et al (2011), Macdonald-Wallis et al (2011), Sawka et al (2013) and Latkin and Knowlton (2015) are in agreement that exposure to social media content from people that are close to the user (such as friends, family members, neighbours, as well as colleagues) significantly impacts on the health behaviour of social media users. Jattamart and Leelasantitham (2019) carried out a study to examine the intentions of patients who have severe depressive disorders and family caregivers to alter their health behaviour and lifestyle through social media influences and reported that there is a significant association between social lifestyle interventions and change in health behaviour for both patients and caregivers. Earlier studies by Young et al (2015) and Maher et al (2015) also reported that social media interventions are effective in influencing health behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our study the use of social media as a source of information was also significantly associated with preventive behavior for COVID-19. Now days the world has become a global village where everyone can share information and learn about new things in the world being at his/ her residence while social influences are primary factor in the adoption of health behaviors [19]. According to findings from a study conducted on effect of medias, media not only provides new information that persuades individuals to accept it but also can informs listeners about what others learn, thus facilitates preventive behavior [20].…”
Section: Plos Onementioning
confidence: 99%
“…Novel-coronavirus disease (COVID- 19) is currently a public health emergency of international and local concerns [1]. The coronavirus belongs to a family of nidovirus that may cause various symptoms such as cough, fever, breathing difficulty, and lung infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are researches studied to the process of changing health behaviors using the I-Change Model (Hein de Vries, Mesters, Van de Steeg and Honing, 2005) including sleep behavior (Cassoff et al, 2014), smoking cessation (Rüther et al, 2015), alcohol consumption (van der Wulp et al, 2013). Moreover, some studies confirm that the possibility of lifestyle interventions by using SM is an influence on health behaviors in depressed patients (Jattamart and Leelasantitham, 2019). The results only explain the relationship between factors and intentions, but as yet there have been no studies into the relationship between change health behaviors, content, and the risk of both privacy and unreliability of information on SM.…”
Section: Introductionmentioning
confidence: 99%